2015
DOI: 10.1007/s40261-015-0364-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Endocrine Therapy on Cognitive Functions of Breast Cancer Patients: A Systematic Review

Abstract: ET among breast cancer patients seems to negatively alter the cognitive outcomes of breast cancer patients. However, the methodological heterogeneity of the included studies, as well as the relatively small follow-up period, render imperative the conduct of further studies in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
0
29
1
Order By: Relevance
“…These findings, although not confirmatory, may indicate that ET, when used as part of a multi-modal treatment regimen, may not, by itself, be associated with cognitive dysfunction. A recent meta-analysis concluded that further longitudinal study of endocrine therapy on cognition in women treated for breast cancer is needed to more conclusively establish this complex relationship (Bakoyiannis et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…These findings, although not confirmatory, may indicate that ET, when used as part of a multi-modal treatment regimen, may not, by itself, be associated with cognitive dysfunction. A recent meta-analysis concluded that further longitudinal study of endocrine therapy on cognition in women treated for breast cancer is needed to more conclusively establish this complex relationship (Bakoyiannis et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, eight reviews have been published addressing the association of hormone therapy with cognitive impairment in breast cancer patients [20■■, 21■■, 2226, 27■], demonstrating high interest in this topic. In this section, emphasis will be placed on the two systematic reviews and a recent narrative review [21■■].…”
Section: Effects Of Ht In Women With Breast Cancermentioning
confidence: 99%
“…A systematic review by Bakoyiannis et al [27] includes 12 studies published before July 2015. Studies contrasting hormone therapy with no hormone therapy patients or healthy controls were mixed with studies contrasting different hormone therapy regimens (SERMs vs. aromatase inhibitors).…”
Section: Effects Of Ht In Women With Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms, generally known as chemobrain or chemofog, are experienced by a lot of women cured with chemotherapy [4]. Bakoyiannis, and colleagues [12] conducted a systematic review on the impact of endocrine therapy on cognitive functions of breast cancer patients. They especially investigated difficulties in five cognitive domains: verbal memory, verbal fluency, attention and working memory, motor speed and psychomotor speed.…”
Section: Introductionmentioning
confidence: 99%